1967
DOI: 10.1017/s0022112067001958
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional flow near a two-dimensional stagnation point

Abstract: This paper shows the existence of a three-dimensional solution of the boundary-layer equations of viscous incompressible flow in the immediate neighbourhood of a two-dimensional stagnation point of attachment. The numerical solution has been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

1972
1972
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 1 publication
2
23
1
Order By: Relevance
“…Full numerical solution of the system also confirms the restriction on α , ie, solutions do exist only in the range −1< α < ∞ . This is also reported in the studies of Davey and Schofield . These numerical solutions always compliment the asymptotic solutions qualitatively, and hence the same results have not been reproduced.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Full numerical solution of the system also confirms the restriction on α , ie, solutions do exist only in the range −1< α < ∞ . This is also reported in the studies of Davey and Schofield . These numerical solutions always compliment the asymptotic solutions qualitatively, and hence the same results have not been reproduced.…”
Section: Resultssupporting
confidence: 63%
“…This is also reported in the studies of Davey and Schofield. 3 These numerical solutions always compliment the asymptotic solutions qualitatively, and hence the same results have not been reproduced. Also, in Figures 5 and 6, the wall shear stresses ′′ (0) and g ′′ (0) are compared with the asymptotic solutions and found that results are agreeing well.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…for Y † = O(1), with θ and A given asymptotically by (27), we are in a position to calculate the required exponentially small correction term , which satisfies…”
Section: Analysis For γ → ∞ (Small Suction or Injection)mentioning
confidence: 99%
“…Coefficients in the Series θ ∼ N 0 θ n µ n and A ∼ N 0 A n µ n , Whose First Few Terms are Given in (27), and Coefficients ψ n in (42) n θ n A n ψ n…”
Section: Tablementioning
confidence: 99%